MEMAHAMI KONSEP AL-FALĀH MELALUI UPAYA PENGUATAN KETAHANAN PANGAN DALAM WORLD ISLAMIC ECONOMIC FORUM (WIEF) - Farida, Ulfa Jamilatul (Journal of Islamic Economics Lariba, 2015)
Global food crises occurred post 2008 have clearly figured out the susceptibility of food security of world countries not only in poor countries but also welfare countries. World Bank data shows that there are millions of hungry people everyday. Referring to FAO data, it is known that the buried countries in the world caused by food are primarily faced by Muslim countries. This research aims to study strengthening food security in Muslim countries and resolution mechanism. Food problem is a common problem that is difficult to be overcome by each country alone. That is why a cooperation mode becomes important to overcome food problem of Muslim countries. Food problem is economic problem both conventional and Islamic economic. In Islamic economic aiming to realize al-falah, food sufficiency is a primer condition in gaining the aim. World Islamic Economic Forum is international organization of Muslim world which concerned to food problem. Therefore, it is very relevant for this international organization to be subject of research. Starting studying on condition of food security in Muslim world and food in a global context, research questions will be discussed by using operational frame in gaining al-falāh and through integration of Muslim world and representative concept of food security. Technically this research is using double research strategy mutually combining quantitative and qualitative approach to gain sharp analyses. The result of the study is strengthening food security in Muslim world done by World Islamic Economic Forum is significant first step by availability of Memorandum of Agreement (MoA) among Muslim countries, mutually cooperation of agriculture investment, and effort to upgrade the potentiality of each Muslim countries by conductively trade cooperation. The process of gaining al-falāh is manifested in effort step to fulfill a sufficiency of food in Muslim world.